Metallization method for homogeneous oxide ceramic surface

By pretreating and depositioning the ceramic surface to form a modified titanium dioxide sol film and preparing metallized slurry, the problems of poor metallization bonding force and poor high and low temperature resistance on the ceramic surface are solved, and metallized ceramics with high binding force and strength are realized, which are suitable for applications in complex environments.

CN119859069AActive Publication Date: 2025-04-22SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS

Patent Information

Application Number
CN202510355885.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-22
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

The metallization methods on the existing ceramic surfaces have problems such as poor binding force, low compression shear strength and poor high and low temperature cycle resistance, which limits the application of ceramics in complex environments.

Method used

A specific method is used to pretreat and deposition the ceramic surface to form a modified titanium dioxide sol film, and a metallized slurry is prepared to achieve high binding force and strength metallized ceramics.

Benefits of technology

It realizes high bonding force between the ceramic matrix and the metal coating, improves the compression shear strength and high and low temperature cycle resistance, and enhances the application of ceramics in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a method for metallizing a homogeneous oxide ceramic surface, and belongs to the technical field of ceramic metallization. The metallization method comprises the steps of pretreatment, primary deposition, metallization slurry preparation, coating and sintering. The primary deposition comprises the following steps: putting the pretreated ceramic into modified titanium dioxide sol, drying and calcining to obtain primarily deposited ceramic; a preparation method of the modified titanium dioxide sol comprises the following steps: adding tetrabutyl titanate into absolute ethyl alcohol, and then adding formylated alumina fibers to obtain a reaction solution A; adding deionized water and glacial acetic acid into absolute ethyl alcohol to obtain a reaction solution B; adding the reaction liquid A into the reaction liquid B, heating to 44-48 DEG C, adding 4-vinyl aniline, and carrying out heat preservation and stirring to obtain titanium dioxide sol; by adopting the metallization method disclosed by the invention, the uniformity is good, the binding force between the ceramic and the metal coating is strong, the compression-shear strength is high, and the high and low temperature cycle resistance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic metallization, and in particular relates to a method for metallizing the surface of a homogeneous oxide ceramic. Background Art

[0002] With the development of science and technology, the application of shielding materials and antennas is becoming more and more extensive, and at the same time, the requirements for shielding materials and antennas are becoming higher and higher; as electronic equipment is developing towards miniaturization, lightweight and high performance, traditional metal shielding has exposed many disadvantages. It is easy to corrode in complex environments, affecting the shielding performance and shortening the service life of the equipment; antennas are key components in wireless communication systems, and they are required to have high stability and resistance to harsh environments.

[0003] Ceramics have excellent properties such as high hardness, high strength, good insulation, high temperature resistance and corrosion resistance, and play an important role in the fields of electrical electronics, aerospace, mechanical manufacturing, medical and construction. However, ceramics themselves are insulators, have the defect of non-conductivity, and are difficult to directly connect with metal parts, limiting their further expansion in electrical connection, heat conduction and structural integration application scenarios.

[0004] Metallization is a ceramic surface treatment technology, which means forming a dense, uniform and strong metal layer on the ceramic surface, thus giving the ceramic material metal properties that it does not originally have. Through metallization treatment, the metallization layer can be used as an intermediate layer to achieve reliable connection between ceramic and metal; it can also give the ceramic surface electrical conductivity, thermal conductivity, and improve the wear resistance and corrosion resistance of the ceramic surface, thereby extending the service life of the ceramic; Ceramics that have undergone metallization treatment can meet the requirements of shielding materials, antennas, etc. for use under complex working conditions. Metallization is of great significance in broadening the application scope of ceramics.

[0005] At present, the main methods for metallization of ceramic surfaces include sintered metal powder method, thin film method and chemical plating method; The sintered metal powder method is to mix metal powder with a binder and then coat it on the ceramic surface, and then sinter the metal powder at high temperature to form a metal layer on the ceramic surface. However, this method has the defect of poor bonding strength between the metal layer and the ceramic matrix, and the metal layer is prone to fall off during use, thereby shortening the service life. In addition, high-temperature sintering will reduce the mechanical properties of the ceramic, etc., narrowing the scope of use of ceramic products. The thin film method uses chemical vapor deposition or physical vapor deposition to deposit a thin metal layer on the ceramic surface. It can obtain a uniform and dense metallization layer, but its equipment cost is high and its process is relatively complicated.

[0006] Chemical plating utilizes redox reactions to deposit a metal layer on the ceramic surface. This method is low-cost, but the bonding force of the metallized layer is weak, and the chemically plated metal layer is easily oxidized at high temperatures, affecting its applicability at high temperatures.

[0007] With the development of technology, there is also existing technology that metallizes ceramics through the sol-gel method, but the metallized ceramics obtained therefrom have the defects of poor bonding between the ceramic matrix and the metallization layer, low compressive shear strength, and poor high and low temperature cycle resistance. Summary of the invention

[0008] In order to solve the technical problems existing in the prior art, the present invention provides a method for metallizing the surface of a homogeneous oxide ceramic, which has good uniformity, strong bonding between the ceramic substrate and the metal coating, high compressive shear strength, excellent high and low temperature cycle resistance, and strong applicability in complex environments.

[0009] A method for metallizing a homogeneous oxide ceramic surface includes pretreatment, primary deposition, preparation of metallization slurry, coating and sintering steps, as follows: The oxide ceramic is one of alumina ceramic, quartz ceramic and zirconia ceramic; 1. Pre-treatment The ceramic is placed in 6-10 times the mass of acetone, the temperature is increased to 53-60°C, and ultrasonic treatment is performed, the ultrasonic time is 12-18 minutes, the ultrasonic power is 132-146W, and the ultrasonic frequency is 27-35kHz. After the ultrasonic treatment is completed, it is filtered out, and then it is put into 6-10 times the mass of sodium hydroxide solution, and the ultrasonic treatment is continued, the ultrasonic power and frequency are kept unchanged, and the ultrasonic time is controlled to be 22-28 minutes. After the ultrasonic treatment is completed, it is filtered out, and then washed with deionized water until the washing liquid is neutral, and dried to obtain a pre-treated ceramic; The mass concentration of the sodium hydroxide solution is 8-12%.

[0010] 2. One-time deposition The pre-treated ceramic is placed in a modified titanium dioxide sol, the modified titanium dioxide sol completely immerses the pre-treated ceramic, the pulling speed is controlled to be 2.5-3.5 cm / min, a titanium dioxide sol film is obtained on the surface of the pre-treated ceramic, and then dried at 62-67°C for 11.5-12.5 hours, and then put into a calcining furnace, and heated to 345-355°C at a rate of 2.6-3.3°C / min, and kept warm for 12-18 minutes, and then heated to 516-523°C at a rate of 1.2-1.7°C / min, and kept warm for 1.4-1.6 hours, to obtain a ceramic after primary deposition; The preparation method of the modified titanium dioxide sol comprises the following steps: adding tetrabutyl titanate to anhydrous ethanol, then adding aldehyde-modified alumina fiber, stirring evenly to obtain a reaction solution A; adding deionized water and glacial acetic acid to the anhydrous ethanol, stirring evenly to obtain a reaction solution B; slowly adding the reaction solution A to the reaction solution B, controlling the adding rate to be 0.4-0.6 g / min, and continuing to stir for 27-34 min after the adding is completed. After the stirring is completed, heating to 44-48° C. at a rate of 0.7-1.2° C. / min, adding 2.0-2.4 g 4-vinylaniline, and stirring at the temperature for 32-38 min. After the stirring is completed, the titanium dioxide sol is obtained. In the reaction solution A, the mass ratio of anhydrous ethanol, tetrabutyl titanate, and aldehyde-modified alumina fiber is 67.4-68.5:32.2-32.7:5.3-5.8; In the reaction solution B, the mass ratio of anhydrous ethanol, deionized water and glacial acetic acid is 106-112:10.0-10.4:10.3-10.8; The mass ratio of the reaction solution B, the reaction solution A and 4-vinylaniline is 126.3-133.2:104.9-106.7:2.0-2.4; The preparation method of the aldehyde-modified alumina fiber comprises placing the alumina fiber in a sodium hydroxide solution, soaking it at 70-74° C. for 1.8-2.2 hours, filtering it out and drying it to obtain the soaked alumina fiber; placing the soaked alumina fiber in an ethanol solution, stirring it evenly, adding a cinnamaldehyde solution, stirring and reacting it at 43-47° C. for 1.8-2.2 hours, then adding sodium borohydride, stirring and reacting it at 3.5-4.6° C. for 2.7-3.4 hours, and filtering, washing and drying it after the reaction is completed to obtain the aldehyde-modified alumina fiber; The alumina fiber has a diameter of 3.2-3.6 μm and a length of 13-16 μm; The mass ratio of the alumina fiber to the sodium hydroxide solution is 9.5-10.4:78.6-83.5; The mass concentration of the sodium hydroxide solution is 13-16%; After the immersion, the mass ratio of the alumina fiber, the ethanol solution, the cinnamaldehyde solution, and the sodium borohydride is 4.7-5.2:56-63:21.7-23.2:1.7-2.2; The mass concentration of the ethanol solution is 16-20%; The cinnamaldehyde solution is a mixture of cinnamaldehyde and a 10-13wt% ethanol solution, and the mass ratio of the cinnamaldehyde to the 10-13wt% ethanol solution is 1.2:8.2-8.8.

[0011] 3. Preparation of metallization slurry Molybdenum powder, manganese powder, aluminum oxide powder, barium carbonate powder, calcium oxide powder, zirconium oxide powder and boron oxide powder are mixed, and then anhydrous ethanol is added for ball milling, the ball milling time is 7.6-8.2h, the ball milling speed is 77-85rpm, and the ball-to-material ratio is 2-4:1. After the ball milling, silane coupling agent A-186 is added, and the ball milling is continued for 3.8-4.2h, and the ball milling speed is 115-127rpm. After the ball milling, the pre-treated composite powder is obtained by filtering, washing and drying; ethyl cellulose, pinene alcohol, glycerol and glyceryl monostearate are mixed, and then heated in a water bath until they are completely dissolved to obtain an additive; the pre-treated composite powder and the additive are mixed, and then ultrasonic treatment is performed, the ultrasonic time is 27-34min, the ultrasonic frequency is 32-37kHz, and the ultrasonic power is 156-165W. After the ultrasonic treatment, a metallization slurry is obtained; The mass ratio of the molybdenum powder, manganese powder, aluminum oxide powder, barium carbonate powder, calcium oxide powder, zirconium oxide powder, boron oxide powder, anhydrous ethanol and silane coupling agent A-186 is 62.6-63.2: 20.5-21.4: 7.3-7.8: 0.6-1.0: 2.2-2.7: 0.3-0.5: 1.6-2.0: 196-206: 7.2-7.8; The mass ratio of the ethyl cellulose, terpineol, glycerol and glyceryl monostearate is 1.0-1.4:17.0-17.5:1.8-2.2:0.7-1.0; The mass ratio of the pretreated composite powder to the added auxiliary agent is 96.6-97.4:20.8-21.5.

[0012] 4. Coating and sintering The metallization slurry is screen-printed onto the ceramic surface after the primary deposition, and the coating thickness is controlled to be 28-32 μm. After coating, it is dried at 108-113°C, and after naturally cooled to room temperature, it is heated to 610-630°C at a rate of 9.5-10.5°C / min in a nitrogen atmosphere, and kept warm for 17-25min, then heated to 1080-1130°C at a rate of 4.2-5.5°C / min, and kept warm for 13-20min, then heated to 1400-1420°C at a rate of 2.0-2.8°C / min, and kept warm for 55-65min, then cooled to 720-740°C at a rate of 5.8-6.2°C / min, and kept warm for 35-45min, and finally cooled to 380-410°C at a rate of 1.8-2.2°C / min, and cooled to room temperature with the furnace to complete the metallization step to obtain the metallized ceramic.

[0013] Compared with the prior art, the present invention has achieved the following beneficial effects: 1. The present invention adopts a specific method to metallize the ceramic surface. First, the substrate is pre-treated to remove organic and inorganic pollutants on the ceramic surface, and the ceramic surface is activated to enhance the adhesion of the subsequent coating. Then, a modified titanium dioxide sol is used for a deposition to form a uniform and dense titanium dioxide coating on the ceramic surface, which is conducive to the attachment and bonding of the subsequent metallization slurry. The modified titanium dioxide sol includes aldehyde-modified alumina fiber. Specifically, the alumina fiber is firstly treated with alkali to make its surface contain more hydroxyl groups, and then aldehyde groups are introduced to react with hydroxyl groups to introduce aldehyde groups to the surface of the alumina fiber. Sodium borohydride further reduces and stabilizes the reaction system, so that the aldehyde groups are stably connected to the surface of the alumina fiber. 4-vinylaniline is also introduced into the modified titanium dioxide sol. The aldehyde groups of the aldehyde-modified alumina fiber can react with 4-vinylaniline to undergo Schiff base reaction. It forms a stable three-dimensional structure in the titanium dioxide sol, thereby improving the stability of the modified titanium dioxide sol, and the formaldehyde-modified alumina fiber can be embedded in the microscopic pore structure of the ceramic surface, increasing the physical anchoring points, greatly improving the bonding force between the modified titanium dioxide sol and the ceramic matrix, and finally improving the strength of the coating in the subsequent sintering process, ensuring the high and low temperature cycle resistance of the coating; in the step of preparing the metallization slurry, the powder is first pretreated with an epoxy silane coupling agent, so that the surface of the pretreated composite powder contains more epoxy groups, so that when it is coated on the ceramic after the first deposition, it can react with the amino group of the modified titanium dioxide sol, thereby enhancing the bonding force between the metallization slurry and the ceramic, combined with the addition of additives, the homogeneity of the coating is guaranteed, the reflectivity is improved, and finally the coating has good stability, high bonding force with the ceramic, and excellent applicability in complex environments such as high and low temperature cycles; 2. The metallized ceramic obtained by metallizing a 99 alumina ceramic substrate using the metallization method of the present invention has a bonding strength of 51.2-53.6 MPa, a compressive shear strength of 24.4-27.2 MPa, and a visible light reflectivity of 70-75% in the range of 380-780 nm; 3. The metallized ceramic obtained by metallizing a 99 alumina ceramic substrate using the metallization method of the present invention is heated to 1500°C at a rate of 30°C / min, kept warm for 1.0h, and then reduced to 20°C at a rate of 50°C / min, and kept warm for 1.0h. The above operation is regarded as one cycle. After 20 cycles, the mass change rate is 0.14-0.19%, the bonding strength is 47.6-50.5MPa, and the compressive shear strength is 13.6-16.3MPa. DETAILED DESCRIPTION

[0014] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.

[0015] The oxide ceramic is one of alumina ceramic, quartz ceramic and zirconia ceramic.

[0016] Example 1 1. Pre-treatment The ceramic was placed in 6 times the mass of acetone, the temperature was raised to 53°C, and ultrasonic treatment was performed. The ultrasonic time was 12 min, the ultrasonic power was 132 W, and the ultrasonic frequency was 27 kHz. After the ultrasonic treatment, it was filtered out and then put into 6 times the mass of 8wt% sodium hydroxide solution. The ultrasonic treatment was continued, the ultrasonic power and frequency were kept unchanged, and the ultrasonic time was controlled to be 22 min. After the ultrasonic treatment, it was filtered out and then washed with deionized water until the washing liquid was neutral. After drying, the pre-treated ceramic was obtained.

[0017] 2. One-time deposition The pre-treated ceramic was placed in a modified titanium dioxide sol, the modified titanium dioxide sol completely immersed the pre-treated ceramic, the pulling speed was controlled to be 2.5 cm / min, a titanium dioxide sol film was obtained on the surface of the pre-treated ceramic, and then dried at 62°C for 12.5 hours, and then put into a calcining furnace, heated to 345°C at a rate of 2.6°C / min, kept warm for 18 minutes, and then heated to 516°C at a rate of 1.7°C / min, kept warm for 1.6 hours, to obtain a ceramic after primary deposition; The preparation method of the modified titanium dioxide sol is as follows: add 32.2g of tetrabutyl titanate to 67.4g of anhydrous ethanol, then add 5.3g of aldehyded alumina fiber, stir evenly to obtain a reaction solution A; add 10.0g of deionized water and 10.3g of glacial acetic acid to 106g of anhydrous ethanol, stir evenly to obtain a reaction solution B; slowly add 104.9g of reaction solution A to 126.3g of reaction solution B, control the addition rate to be 0.4g / min, continue to stir for 27min after the addition is completed, heat to 44°C at a rate of 0.7°C / min after the stirring is completed, add 2.0g of 4-vinylaniline, keep warm and stir for 32min, and obtain the titanium dioxide sol after the stirring is completed; The preparation method of the aldehyde-modified alumina fiber is as follows: 9.5 g of the alumina fiber is placed in 78.6 g of a 13 wt% sodium hydroxide solution, soaked at 70° C. for 2.2 h, filtered out and dried to obtain the soaked alumina fiber; 4.7 g of the soaked alumina fiber is placed in 56 g of a 16 wt% ethanol solution, stirred evenly, 21.7 g of a cinnamaldehyde solution is added, stirred at 43° C. for 2.2 h, and then 1.7 g of sodium borohydride is added, stirred at 3.5° C. for 3.4 h, and after the reaction is completed, filtered, washed and dried to obtain the aldehyde-modified alumina fiber; The diameter of the alumina fiber is 3.2 μm and the length is 13 μm; The cinnamaldehyde solution is a mixture of cinnamaldehyde and a 10wt% ethanol solution, and the mass ratio of the cinnamaldehyde to the 10wt% ethanol solution is 1.2:8.2; 3. Preparation of metallization slurry 62.6g of molybdenum powder, 20.5g of manganese powder, 7.3g of aluminum oxide powder, 0.6g of barium carbonate powder, 2.2g of calcium oxide powder, 0.3g of zirconium oxide powder, and 1.6g of boron oxide powder were mixed, and then 196g of anhydrous ethanol was added for ball milling. The ball milling time was 7.6h, the ball milling speed was 85rpm, and the ball-to-material ratio was 2:1. After the ball milling, 7.2g of silane coupling agent A-186 was added, and the ball milling was continued for 3.8h. The ball milling speed was 127rpm. After the ball milling, the pre-treated composite powder was obtained by filtering, washing, and drying; 1.0g of ethyl cellulose, 17.0g of pine alcohol, 1.8g of glycerol, and 0.7g of glyceryl monostearate were mixed, and then heated in a water bath until all dissolved to obtain an additive; 96.6 g of the pretreated composite powder was mixed with 20.8 g of the additive, and then subjected to ultrasonic treatment. The ultrasonic time was 27 min, the ultrasonic frequency was 32 kHz, and the ultrasonic power was 156 W. After the ultrasonic treatment, a metallization slurry was obtained.

[0018] 4. Coating and sintering The metallization slurry was screen-printed onto the ceramic surface after the primary deposition, and the coating thickness was controlled to be 28 μm. After coating, it was dried at 108°C. After naturally cooled to room temperature, it was heated to 610°C at a rate of 9.5°C / min in a nitrogen atmosphere, kept warm for 25 minutes, then heated to 1080°C at a rate of 4.2°C / min, kept warm for 20 minutes, then heated to 1400°C at a rate of 2.8°C / min, kept warm for 65 minutes, then cooled to 720°C at a rate of 6.2°C / min, kept warm for 45 minutes, and finally cooled to 410°C at a rate of 1.8°C / min. It was cooled to room temperature with the furnace to complete the metallization step and obtain metallized ceramics.

[0019] Example 2 1. Pre-treatment The ceramic substrate was placed in 8 times the mass of acetone, the temperature was raised to 56°C, and ultrasonic treatment was performed. The ultrasonic time was 15 minutes, the ultrasonic power was 140W, and the ultrasonic frequency was 31kHz. After the ultrasonic treatment, it was filtered out and then put into 8 times the mass of 10wt% sodium hydroxide solution. The ultrasonic treatment was continued, the ultrasonic power and frequency were kept unchanged, and the ultrasonic time was controlled to be 25 minutes. After the ultrasonic treatment, it was filtered out and then washed with deionized water until the washing liquid was neutral. After drying, the pre-treated ceramic was obtained.

[0020] 2. One-time deposition The pre-treated ceramic was placed in a modified titanium dioxide sol, the modified titanium dioxide sol completely immersed the pre-treated ceramic, the pulling speed was controlled to be 3.0 cm / min, a titanium dioxide sol film was obtained on the surface of the pre-treated ceramic, and then dried at 65°C for 12.0 hours, and then put into a calcining furnace, heated to 350°C at a rate of 3.0°C / min, kept warm for 15 minutes, and then heated to 520°C at a rate of 1.5°C / min, kept warm for 1.5 hours, to obtain a ceramic after primary deposition; The preparation method of the modified titanium dioxide sol is as follows: add 32.5g of tetrabutyl titanate to 68.0g of anhydrous ethanol, then add 5.6g of aldehyded alumina fiber, stir evenly to obtain a reaction solution A; add 10.2g of deionized water and 10.5g of glacial acetic acid to 110g of anhydrous ethanol, stir evenly to obtain a reaction solution B; slowly add 106.1g of reaction solution A to 130.7g of reaction solution B, control the addition rate to be 0.5g / min, continue to stir for 30min after the addition is completed, heat to 46°C at a rate of 1.0°C / min after the stirring is completed, add 2.2g of 4-vinylaniline, keep warm and stir for 35min, and obtain the titanium dioxide sol after the stirring is completed; The preparation method of the aldehyde-modified alumina fiber is as follows: 10.0 g of the alumina fiber is placed in 80.0 g of a 15 wt% sodium hydroxide solution, soaked at 72° C. for 2.0 h, filtered out and dried to obtain the soaked alumina fiber; 5.0 g of the soaked alumina fiber is placed in 60 g of an 18 wt% ethanol solution, stirred evenly, and then 22.5 g of a cinnamaldehyde solution is added, stirred at 45° C. for 2.0 h, and then 2.0 g of sodium borohydride is added, stirred at 4.0° C. for 3.0 h, and after the reaction is completed, filtered, washed and dried to obtain the aldehyde-modified alumina fiber; The diameter of the alumina fiber is 3.5 μm and the length is 15 μm; The cinnamaldehyde solution is a mixture of cinnamaldehyde and a 12wt% ethanol solution, and the mass ratio of the cinnamaldehyde to the 12wt% ethanol solution is 1.2:8.5.

[0021] 3. Preparation of metallization slurry 63.0g of molybdenum powder, 21.0g of manganese powder, 7.6g of aluminum oxide powder, 0.8g of barium carbonate powder, 2.5g of calcium oxide powder, 0.4g of zirconium oxide powder, and 1.8g of boron oxide powder were mixed, and then 200g of anhydrous ethanol was added for ball milling. The ball milling time was 8.0h, the ball milling speed was 80rpm, and the ball-to-material ratio was 3:1. After the ball milling, 7.6g of silane coupling agent A-186 was added, and the ball milling was continued for 4.0h. The ball milling speed was 120rpm. After the ball milling, the pre-treated composite powder was obtained by filtering, washing, and drying; 1.2g of ethyl cellulose, 17.2g of pine alcohol, 2.0g of glycerol, and 0.8g of glyceryl monostearate were mixed, and then heated in a water bath until all dissolved to obtain an additive; 97.1 g of the pretreated composite powder was mixed with 21.2 g of the additive, and then subjected to ultrasonic treatment. The ultrasonic time was 30 min, the ultrasonic frequency was 35 kHz, and the ultrasonic power was 160 W. After the ultrasonic treatment, a metallization slurry was obtained.

[0022] 4. Coating and sintering The metallization slurry is screen-printed onto the ceramic surface after the primary deposition, and the coating thickness is controlled to be 30 μm. After coating, it is dried at 110°C. After naturally cooling to room temperature, it is heated to 620°C at a rate of 10.0°C / min in a nitrogen atmosphere, kept warm for 20 minutes, then heated to 1100°C at a rate of 5.0°C / min, kept warm for 15 minutes, then heated to 1410°C at a rate of 2.5°C / min, kept warm for 60 minutes, then cooled to 730°C at a rate of 6.0°C / min, kept warm for 40 minutes, and finally cooled to 400°C at a rate of 2.0°C / min. It is cooled to room temperature with the furnace to complete the metallization step to obtain metallized ceramics.

[0023] Example 3 1. Pre-treatment The ceramic was placed in 10 times the mass of acetone, the temperature was raised to 60°C, and ultrasonic treatment was performed. The ultrasonic time was 18 minutes, the ultrasonic power was 146W, and the ultrasonic frequency was 35kHz. After the ultrasonic treatment, it was filtered out and then put into 10 times the mass of 12wt% sodium hydroxide solution. The ultrasonic treatment was continued, the ultrasonic power and frequency were kept unchanged, and the ultrasonic time was controlled to be 28 minutes. After the ultrasonic treatment, it was filtered out and then washed with deionized water until the washing liquid was neutral. After drying, the pre-treated ceramic was obtained.

[0024] 2. One-time deposition The pre-treated ceramic was placed in a modified titanium dioxide sol, the modified titanium dioxide sol completely immersed the pre-treated ceramic, the pulling speed was controlled to be 3.5 cm / min, a titanium dioxide sol film was obtained on the surface of the pre-treated ceramic, and then dried at 67°C for 11.5 hours, and then put into a calcining furnace, heated to 355°C at a rate of 3.3°C / min, kept warm for 12 minutes, and then heated to 523°C at a rate of 1.2°C / min, kept warm for 1.4 hours, to obtain a ceramic after primary deposition; The preparation method of the modified titanium dioxide sol is as follows: add 32.7g of tetrabutyl titanate to 68.5g of anhydrous ethanol, then add 5.8g of aldehyded alumina fiber, stir evenly to obtain a reaction solution A; add 10.4g of deionized water and 10.8g of glacial acetic acid to 112g of anhydrous ethanol, stir evenly to obtain a reaction solution B; slowly add 106.7g of reaction solution A to 133.2g of reaction solution B, control the addition rate to be 0.6g / min, continue to stir for 34min after the addition is completed, heat to 48°C at a rate of 1.2°C / min after the stirring is completed, add 2.4g of 4-vinylaniline, keep warm and stir for 38min, and obtain the titanium dioxide sol after the stirring is completed; The preparation method of the aldehyde-modified alumina fiber is as follows: 10.4 g of the alumina fiber is placed in 83.5 g of a 16 wt% sodium hydroxide solution, soaked at 74° C. for 1.8 h, filtered out and dried to obtain the soaked alumina fiber; 5.2 g of the soaked alumina fiber is placed in 63 g of a 20 wt% ethanol solution, stirred evenly, 23.2 g of a cinnamaldehyde solution is added, stirred at 47° C. for 1.8 h, and then 2.2 g of sodium borohydride is added, stirred at 4.6° C. for 2.7 h, and after the reaction is completed, filtered, washed and dried to obtain the aldehyde-modified alumina fiber; The diameter of the alumina fiber is 3.6 μm and the length is 16 μm; The cinnamaldehyde solution is a mixture of cinnamaldehyde and 13wt% ethanol solution, and the mass ratio of the cinnamaldehyde to the 13wt% ethanol solution is 1.2:8.8; 3. Preparation of metallization slurry 63.2g of molybdenum powder, 21.4g of manganese powder, 7.8g of aluminum oxide powder, 1.0g of barium carbonate powder, 2.7g of calcium oxide powder, 0.5g of zirconium oxide powder, and 2.0g of boron oxide powder were mixed, and then 206g of anhydrous ethanol was added for ball milling. The ball milling time was 8.2h, the ball milling speed was 77rpm, and the ball-to-material ratio was 4:1. After the ball milling, 7.8g of silane coupling agent A-186 was added, and the ball milling was continued for 4.2h. The ball milling speed was 115rpm. After the ball milling, the pre-treated composite powder was obtained by filtering, washing, and drying; 1.4g of ethyl cellulose, 17.5g of pine alcohol, 2.2g of glycerol, and 1.0g of glyceryl monostearate were mixed, and then heated in a water bath until all dissolved to obtain an additive; 97.4 g of the pretreated composite powder was mixed with 21.5 g of the additive, and then subjected to ultrasonic treatment. The ultrasonic time was 34 min, the ultrasonic frequency was 37 kHz, and the ultrasonic power was 165 W. After the ultrasonic treatment, a metallization slurry was obtained.

[0025] 4. Coating and sintering The metallization slurry was screen-printed onto the ceramic surface after the primary deposition, and the coating thickness was controlled to be 2 μm. After coating, it was dried at 113°C. After naturally cooled to room temperature, it was heated to 630°C at a rate of 10.5°C / min in a nitrogen atmosphere, kept warm for 17 minutes, then heated to 1130°C at a rate of 5.5°C / min, kept warm for 13 minutes, then heated to 1420°C at a rate of 2.0°C / min, kept warm for 55 minutes, then cooled to 740°C at a rate of 5.8°C / min, kept warm for 35 minutes, and finally cooled to 380°C at a rate of 2.2°C / min. It was cooled to room temperature with the furnace to complete the metallization step and obtain metallized ceramics.

[0026] Comparative Example 1 Based on Example 2, the changes are as follows: In one deposition step, the modified titania sol was replaced by titania sol in equal amounts; The preparation method of the titanium dioxide sol is as follows: add 32.5g of tetrabutyl titanate to 68.0g of anhydrous ethanol, stir evenly to obtain a reaction solution A; add 10.2g of deionized water and 10.5g of glacial acetic acid to 110g of anhydrous ethanol, stir evenly to obtain a reaction solution B; slowly add 106.1g of reaction solution A to 130.7g of reaction solution B, control the addition rate to 0.5g / min, continue stirring for 30min after the addition is completed, and obtain the titanium dioxide sol after the stirring is completed; The rest of the operations are the same.

[0027] Comparative Example 2 Based on Example 2, the changes are as follows: (1) In one deposition step In the preparation method of the modified titanium dioxide sol, the aldehyde-modified alumina fibers are replaced by an equal amount of untreated alumina fibers, wherein the diameter of the alumina fibers is 3.5 μm and the length is 15 μm; (2) In the step of preparing metallization slurry In the preparation method of the pretreated powder, the silane coupling agent A-186 is replaced by anhydrous ethanol in equal amounts; The rest of the operations are the same.

[0028] Experimental performance 99 alumina ceramics were selected as the metallized substrate, and then the metallized substrate was metallized using the methods of Examples 1-3 and Comparative Examples 1-2 to obtain a sample to be tested; 1. Test the bonding strength, compressive shear strength, visible light reflectivity in the range of 380-780nm and high temperature resistance of the test samples. The results are as follows:

[0029] 2. The above-mentioned test sample was heated to 1500℃ at a rate of 30℃ / min, kept warm for 1.0h, then cooled to 20℃ at a rate of 50℃ / min, kept warm for 1.0h. The above operation was one cycle. After 20 cycles, the bonding strength and compressive shear strength were tested again. The results are as follows:

[0030] The present invention adopts a specific method to metallize the ceramic surface. First, the substrate is pre-treated to remove organic pollutants and inorganic pollutants on the ceramic surface, and the ceramic surface is activated to enhance the adhesion of subsequent coatings. Then, a modified titanium dioxide sol is used for deposition to form a uniform and dense titanium dioxide coating on the ceramic surface, which is beneficial to the attachment and bonding of subsequent metallization slurry. The modified titanium dioxide sol includes aldehyde-modified alumina fiber. Specifically, the alumina fiber is firstly subjected to alkali treatment to make its surface contain more hydroxyl groups, and then aldehyde groups are introduced to react with hydroxyl groups to introduce aldehyde groups to the surface of the alumina fiber. Sodium borohydride further reduces and stabilizes the reaction system, so that the aldehyde groups are stably connected to the surface of the alumina fiber. 4-vinylaniline is also introduced into the modified titanium dioxide sol. The aldehyde groups of the aldehyde-modified alumina fiber can react with 4-vinylaniline to undergo Schiff base reaction. A stable three-dimensional structure is formed in the titanium dioxide sol, thereby improving the stability of the modified titanium dioxide sol, and the formaldehyde-modified alumina fiber can be embedded in the microscopic pore structure of the ceramic surface, increasing the physical anchoring points, greatly improving the bonding force between the modified titanium dioxide sol and the ceramic matrix, and ultimately improving the strength of the coating in the subsequent sintering process, ensuring the coating's resistance to high and low temperature cycles; in the step of preparing the metallization slurry, the powder is first pretreated with an epoxy silane coupling agent so that the surface of the pretreated composite powder contains more epoxy groups, so that when it is coated on the ceramic after a single deposition, it can react with the amino group of the modified titanium dioxide sol, thereby enhancing the bonding force between the metallization slurry and the ceramic, combined with the addition of additives, the homogeneity of the coating is guaranteed, the reflectivity is improved, and ultimately the coating has good stability, high bonding force with the ceramic, and excellent applicability in complex environments such as high and low temperature cycles.

[0031] Comparative Example 1 is based on Example 2, except that the modified titanium dioxide sol is replaced by the conventional titanium dioxide sol in equal amounts, and the formaldehyde-containing alumina component and the 4-vinylaniline component are omitted. The titanium dioxide sol cannot form a stable three-dimensional structure, which makes the performance of the titanium dioxide sol unstable. The formaldehyde-containing alumina fiber is omitted, which cannot be embedded in the ceramic surface to enhance the strength of the coating, ultimately resulting in low bonding between the metal and the ceramic. After multiple high and low temperature cycles, the strength performance is greatly reduced, shortening the service life of the metallized ceramic.

[0032] In Comparative Example 2, only untreated alumina fibers are added to the modified titanium dioxide sol. Although the alumina fibers can increase the bonding strength with the ceramic to a certain extent, the alumina fibers have strong agglomeration force and poor dispersibility in the titanium dioxide sol. They cannot cross-link with 4-vinylaniline to form a stable network structure, which makes the modified titanium dioxide sol unstable. In the preparation method of the pretreated powder in Comparative Example 2, the treatment of silane coupling agent A-186 is omitted, which will prevent the metallized slurry from strongly bonding with the ceramic after the first deposition, ultimately reducing the bonding strength between the metal and the ceramic, weakening the compressive shear strength, and poor high and low temperature cycle resistance.

[0033] Unless otherwise specified, all percentages used in the present invention are by mass.

[0034] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for metallizing a homogeneous oxide ceramic surface, characterized in that: It includes pre-treatment, primary deposition, preparation of metallization slurry, coating and sintering steps; The primary deposition step is to place the pre-treated ceramic in a modified titanium dioxide sol, dry it, and then calcine it to obtain a ceramic after primary deposition; The preparation method of the modified titanium dioxide sol comprises the following steps: adding tetrabutyl titanate to anhydrous ethanol, then adding aldehyde-modified alumina fiber, stirring evenly to obtain a reaction solution A; adding deionized water and glacial acetic acid to the anhydrous ethanol, stirring evenly to obtain a reaction solution B; slowly adding the reaction solution A to the reaction solution B, stirring evenly, heating to 44-48° C., adding 4-vinylaniline, and stirring while keeping the temperature constant to obtain the titanium dioxide sol; The pretreated composite powder is mixed with an additive, and then subjected to ultrasonic treatment to obtain a metallization slurry; the preparation method of the pretreated composite powder is as follows: molybdenum powder, manganese powder, aluminum oxide powder, barium carbonate powder, calcium oxide powder, zirconium oxide powder, and boron oxide powder are mixed, and then anhydrous ethanol is added for a first ball milling treatment, and then a silane coupling agent A-186 is added for a second ball milling treatment to obtain the pretreated composite powder.

2. A method for metallizing a homogeneous oxide ceramic surface according to claim 1, characterized in that: The pretreatment step comprises placing the ceramic in 6-10 times the mass of acetone, raising the temperature to 53-60° C., performing ultrasonic treatment, wherein the ultrasonic time is 12-18 min, the ultrasonic power is 132-146 W, and the ultrasonic frequency is 27-35 kHz. After the ultrasonic treatment is completed, filtering out the ceramic, and then placing the ceramic in 6-10 times the mass of sodium hydroxide solution, continuing the ultrasonic treatment, keeping the ultrasonic power and frequency unchanged, and controlling the ultrasonic time to be 22-28 min. After the ultrasonic treatment is completed, filtering out the ceramic, and then washing with deionized water until the washing liquid is neutral, and drying to obtain the pretreated ceramic. The mass concentration of the sodium hydroxide solution is 8-12%.

3. A method for metallizing a homogeneous oxide ceramic surface according to claim 1, characterized in that: The primary deposition step is to place the pre-treated ceramic in a modified titanium dioxide sol, the modified titanium dioxide sol completely immerses the pre-treated ceramic, control the pulling speed to be 2.5-3.5 cm / min, obtain a titanium dioxide sol film on the surface of the pre-treated ceramic, and then dry it at 62-67°C for 11.5-12.5h, then put it into a calcining furnace, heat it to 345-355°C at a rate of 2.6-3.3°C / min, keep it warm for 12-18min, and then heat it to 516-523°C at a rate of 1.2-1.7°C / min, keep it warm for 1.4-1.6h, and obtain the ceramic after primary deposition.

4. A method for metallizing a homogeneous oxide ceramic surface according to claim 1, characterized in that: In the preparation method of the modified titanium dioxide sol, in the reaction solution A, the mass ratio of the anhydrous ethanol, tetrabutyl titanate, and aldehyde-modified alumina fiber is 67.4-68.5:32.2-32.7:5.3-5.8; In the reaction solution B, the mass ratio of anhydrous ethanol, deionized water and glacial acetic acid is 106-112:10.0-10.4:10.3-10.8; The mass ratio of the reaction solution B, the reaction solution A and 4-vinylaniline is 126.3-133.2:104.9-106.7:2.0-2.

4.

5. The method for metallizing the surface of a homogeneous oxide ceramic according to claim 1, characterized in that: The preparation method of the aldehyde-modified alumina fiber comprises the following steps: placing the alumina fiber in a sodium hydroxide solution, soaking it at 70-74° C. for 1.8-2.2 hours, filtering it out and drying it to obtain the soaked alumina fiber; placing the soaked alumina fiber in an ethanol solution, stirring it evenly, adding a cinnamaldehyde solution, stirring and reacting it at 43-47° C. for 1.8-2.2 hours, then adding sodium borohydride, stirring and reacting it at 3.5-4.6° C. for 2.7-3.4 hours, and filtering, washing and drying it after the reaction is completed to obtain the aldehyde-modified alumina fiber.

6. A method for metallizing a homogeneous oxide ceramic surface according to claim 5, characterized in that: The alumina fiber has a diameter of 3.2-3.6 μm and a length of 13-16 μm; The mass ratio of the alumina fiber to the sodium hydroxide solution is 9.5-10.4:78.6-83.5; The mass concentration of the sodium hydroxide solution is 13-16%; After the immersion, the mass ratio of the alumina fiber, the ethanol solution, the cinnamaldehyde solution, and the sodium borohydride is 4.7-5.2:56-63:21.7-23.2:1.7-2.2; The mass concentration of the ethanol solution is 16-20%; The cinnamaldehyde solution is a mixture of cinnamaldehyde and a 10-13wt% ethanol solution, and the mass ratio of the cinnamaldehyde to the 10-13wt% ethanol solution is 1.2:8.2-8.

8.

7. A method for metallizing a homogeneous oxide ceramic surface according to claim 1, characterized in that: In the method for preparing the metallization slurry, the mass ratio of the pretreated composite powder to the added auxiliary agent is 96.6-97.4:20.8-21.

5.

8. A method for metallizing a homogeneous oxide ceramic surface according to claim 1, characterized in that: In the method for preparing the pretreated composite powder, the first ball milling treatment has a ball milling time of 7.6-8.2 h, a ball milling speed of 77-85 rpm, and a ball-to-material ratio of 2-4:1; The secondary ball milling treatment has a ball milling time of 3.8-4.2 hours and a ball milling speed of 115-127 rpm; The mass ratio of the molybdenum powder, manganese powder, aluminum oxide powder, barium carbonate powder, calcium oxide powder, zirconium oxide powder, boron oxide powder, anhydrous ethanol and silane coupling agent A-186 is 62.6-63.2:20.5-21.4:7.3-7.8:0.6-1.0:2.2-2.7:0.3-0.5:1.6-2.0:196-206:7.2-7.

8.

9. A method for metallizing a homogeneous oxide ceramic surface according to claim 1, characterized in that: In the method for preparing the metallization slurry, the method for preparing the additive is to mix ethyl cellulose, terpineol, glycerol and glyceryl monostearate, and then heat them in a water bath until they are completely dissolved to obtain the additive; The mass ratio of the ethyl cellulose, terpineol, glycerol and glyceryl monostearate is 1.0-1.4:17.0-17.5:1.8-2.2:0.7-1.

0.

10. The method for metallizing the surface of a homogeneous oxide ceramic according to claim 1, characterized in that: The coating and sintering steps are as follows: screen printing the metallization slurry onto the ceramic surface after the primary deposition, controlling the coating thickness to be 28-32 μm, drying at 108-113° C. after coating, and naturally cooling to room temperature, heating to 610-630° C. at a rate of 9.5-10.5° C. / min in a nitrogen atmosphere, keeping the temperature for 17-25 min, then heating to 1080-1130° C. at a rate of 4.2-5.5° C. / min, keeping the temperature for 13-20 min, then heating to 1400-1420° C. at a rate of 2.0-2.8° C. / min, keeping the temperature for 55-65 min, then cooling to 720-740° C. at a rate of 5.8-6.2° C. / min, keeping the temperature for 35-45 min, finally cooling to 380-410° C. at a rate of 1.8-2.2° C. / min, cooling to room temperature with the furnace, completing the metallization step, and obtaining the metallized ceramic.

Citation Information

Patent Citations

  • Benzoxazine monomer comprising vinyl benzene structure, and application and preparation method of benzoxazine monomer

    CN104926749A

  • Low-dielectric fused quartz microwave medium ceramic surface metallization method

    CN110563483A

  • Alumina fiber, alumina fiber aggregate, and retaining material for use in exhaust gas purification device

    CN111344443A

  • Al2O3-based ceramic welding sealing component and preparation method thereof

    CN113173797A

  • Alumina fiber thermal insulation material and preparation method thereof

    CN115491921A

Cited By

  • ZrB2 / SiC / TiB2 ultrahigh-temperature ceramic and preparation method thereof

    CN120117907A

  • High-temperature co-sintered multilayer special-shaped ceramic high-temperature sensor and preparation method thereof

    CN120213091A